Blonanserin suppresses impulsive action in rats - Naoya Nishitani; Hitomi Sasamori; Yu Ohmura; Takayuki Yoshida; Mitsuhiro Yoshioka (Elsevier, 2019)
High impulsivity will increase the risk of criminal behavior, drug abuse, and suicide. We chose two drugs by following a strategy recently we proposed for identifying potential anti-impulsivity drugs, and examined the effects on impulsive action in rats by using a 3-choice serial reaction time task. We showed that the administration of blonanserin, an atypical antipsychotic, reduced impulsive actions in a U-shaped manner. 1-(2-Pyriidinyl)-piperazine, an active metabolite of buspirone or tandospirone, also slightly reduced impulsive actions, though it impaired motor functions. These results affirm the validity of our strategy, but require its refinement for developing anti-impulsivity drugs. Keywords: Impulsive behavior, 1-PP, Antipsychotics